Diagnosis of Rickets from Pneumonia - Osman Yeşilbaş; Nazan Ülgen Tekerek; Ülkü Gül Şiraz; Serhat Tekerek; Mevlüt Salim (Galenos Yayinevi, 2018)
Rickets is a group of diseases presenting with decreased growth rate and skeletal deformities due to diminished endochondral calcification. Despite vitamin D supplementation programs, nutritional rickets is an important public health problem in developing countries. Lower respiratory tract infections and nutritional rickets associated with vitamin D deficiency are both common in children younger than five years of age. Studies especially in developing countries have shown the association between nutritional rickets and lower respiratory tract infections. In this paper, we report a patient with nutritional rickets who was referred with pneumonia and discuss rickets-pneumonia association in the light of the literature.